Global Trends on the Use of Artificial Intelligence in Nursing: A Descriptive and Evaluative Bibliometric Analysis Study - Fatma Azizoğlu; Banu Terzi (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: There is a need to examine the use of artificial intelligence in the branch of nursing and to investigate thecharacteristics of the research conducted in this field.Aim: The aimed was to examine the characteristics of the current knowledge structure and development process in thefield of the use of artificial intelligence in nursing.Method: In the descriptive and evaluative bibliometric analysis study, data were obtained from Web of Science database.All relevant studies conducted between 2004 and 2023 were included in the study. Data analysis was performed usingR Biblioshniy software. Two hundred seventy-three studies were included in the study.Results: The most publications (n = 86, 31.50%) were made in this field in 2022. The most productive author in the field of nursing and artificial intelligence was Topaz, Maxim. The prominent topics in the studies were "virtual reality, artificial intelligence, nursing, machine learning, simulation, nursing education, education, pain, nursing students, natural language processing, nurses, robotics, deep learning and mental health".Conclusion: There has been a significant increase in the number of studies on the use of artificial intelligence in nursingand this area offers an active field of study for nursing researchers